Gamified Lesson Designs in Fostering Positive Washback: A Case Study from Bangladesh - Abtahee, H. (University of Jaffna, 2025)
The study conducted at two major private universities in Bangladesh examines the impact of gamified lesson design on teaching and learning outcomes by enhancing positive washback in language instruction. In tertiary-level language courses, washback - the influence of examinations on teaching and learning- significantly affects educational efficacy. Conventional pedagogical approaches, typically centred on the instructor and inflexible in the application, may not effectively synchronize educational processes with intended evaluation results, particularly for Generation Z students who exhibit diminished attention spans and require engaging learning settings. Gamified lesson design, using platforms or apps such as Quizizz, Kahoot!, Gimkit, Quizlet, Prodigy, Duolingo, and Mentimeter, has proved greatly promising in engaging the students, encouraging their participation, and making their classrooms more interactive, as it allows space in the methodology for quizzes, surveys, discussions, problem-solving tasks, and many more activity ideas. This study takes a close look at how teachers perceive gamification to align teaching methods with assessment goals and, at the same time, boost the learners’ motivation to attain the desired learning outcomes. The aim is to understand whether gamified lessons with real-time feedback, points, badges, leaderboards, challenges and levels can motivate the students to meet learning objectives while promoting positive washback. The research also explores how tertiary-level EFL instructors are encouraged to incorporate gamification into their lesson plans. It examines their challenges and the role various demographic factors could play in attaining the desired course outcomes by boosting the learners’ motivation. While addressing these areas, the study aims to demonstrate how gamification can help improve language learning and align teaching with assessments.
Keywords: Gamification; Washback; English as a Foreign Language; Tertiary education; Assessment